PENGARUH EKSTRAK DAUN PEPAYA (CARICA PAPAYA L.) TERHADAP KADAR HEMOGLOBIN DAN HEMATOKRIT PADA REMAJA PUTRI ANEMIA - Faridah, Salsabila Nur; Rahayu, Sri; Suwondo, Ari (Poltekkes Kemenkes Bandung, 2025)
Adolescent girls often experience anemia, a condition in which red blood cell count or hemoglobin concentration falls below normal levels, especially during puberty. Globally, anemia affects 40% of children aged 6–59 months, 37% of pregnant women, and 30% of women aged 15–49 years. California papaya leaves (Carica papaya L.) are a nutritious vegetable that may help accelerate anemia reduction efforts. This study aimed to prove that administering papaya leaf extract at a dose of 800 mg/day affects hemoglobin and hematocrit levels in anemic adolescent girls. This true experimental study used a randomized pretest-posttest control group design. Conducted from December 1–20, 2024, at Junior High School 2 Balong, Ponorogo, Indonesia, it involved 46 anemic adolescent respondents who met the inclusion and exclusion criteria. They were divided into two groups: 23 participants in the intervention group, who received 800 mg of papaya leaf extract along with 60 mg of iron tablets, and 23 in the control group, who received only 60 mg of iron tablets for 14 days. Data processing was conducted using SPSS version 27, with statistical analysis performed using the parametric dependent T-Test and independent T-Test. The results showed that the intervention group experienced an average increase in hemoglobin levels of 0.444 g/dL and hematocrit levels of 0.39. In conclusion, administering 800 mg of papaya leaf extract significantly affects hemoglobin and hematocrit levels in anemic adolescent girls, supporting efforts to reduce anemia prevalence.